SPEAKING SKILL DEVELOPMENT THROUGH EMI: EVIDENCE FROM A SURAKARTA INTERNATIONAL SCHOOL - Anisa Seta Warti; Diah Kristina; Joko Nurkamto (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study investigates the influence of English Medium Instruction (EMI) on the development of students’ speaking competence in an international high school in Surakarta. As English mastery becomes an essential skill in the globalized era, understanding how EMI shapes speaking proficiency is increasingly urgent for Indonesian education. Using a qualitative case study design, data were collected through classroom observations, interviews, and speaking assessments. Findings reveal that students face persistent challenges in grammar and pronunciation, while low confidence and limited academic vocabulary hinder active participation in EMI-based classrooms. The study also identifies role-play as the most effective technique for enhancing speaking performance within EMI contexts. This research offers novel insights into how EMI operates in Indonesian international schooling and contributes both theoretically and practically by informing teachers and policymakers on strategies to optimize EMI implementation and strengthen students’ speaking competence.